IgE responses to exogenous and endogenous allergens in atopic dermatitis patients under long‐term systemic cyclosporine A treatment. Issue 1 (17th September 2015) - Lucae, S.; Schmid‐Grendelmeier, P.; Wüthrich, B.; Kraft, D.; Valenta, R.; Linhart, B.
Abstract: Atopic dermatitis (AD) patients mount IgE antibody responses to a variety of environmental allergens and also to autoantigens. We analyzed serum samples from four AD patients who had received oral cyclosporine A (CyA) treatment for up to 17 months regarding IgE autoreactivity to nitrocellulose‐blotted human epithelial cell extracts and IgE levels to environmental allergens by quantitative ImmunoCap measurements. Skin inflammation was assessed by SCORAD. During full‐dose treatment, a strong reduction in T‐cell‐mediated skin symptoms was observed which reappeared when CyA treatment was reduced or stopped. The intensity of IgE autoreactivity seemed to follow skin inflammation as it was reduced during full‐dose treatment and increased upon inflammation. Interestingly, IgE levels to exogenous allergens were boosted by allergen exposure, declined thereafter, and seemed to be unaffected by CyA. Our data thus indicate that allergen‐specific IgE production is boosted by allergen contact and cannot be reduced by CyA‐mediated T‐cell suppression.